2016
DOI: 10.1002/bjs.10126
|View full text |Cite
|
Sign up to set email alerts
|

Association between underestimation of tumour size by imaging and incomplete excision in breast-conserving surgery for breast cancer

Abstract: Underestimation of tumour size by current imaging techniques is a major factor associated with incomplete excision in women undergoing BCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 50 publications
3
10
0
Order By: Relevance
“…29,32 Other studies, similar to the current findings, have shown that the diffuse DCIS growth patterns such as micropapillary and cribriform types, high nuclear grade DCIS with comedo type necrosis and high-risk VNPI are factors associated with an increased rate of re-excisions. [31][32][33][34] The current study shows that half of the patients with DCIS who underwent re-excision, due to positive or close surgical margins, were of low and intermediate grade. This practice might have an impact on the pending outcome of recent trials for more conservative management of low-risk DCIS.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…29,32 Other studies, similar to the current findings, have shown that the diffuse DCIS growth patterns such as micropapillary and cribriform types, high nuclear grade DCIS with comedo type necrosis and high-risk VNPI are factors associated with an increased rate of re-excisions. [31][32][33][34] The current study shows that half of the patients with DCIS who underwent re-excision, due to positive or close surgical margins, were of low and intermediate grade. This practice might have an impact on the pending outcome of recent trials for more conservative management of low-risk DCIS.…”
Section: Discussionsupporting
confidence: 87%
“…The need to perform further surgery, re‐excision or completion mastectomy, is governed predominantly by what is regarded as a minimum free resection margin. Positive margins are partly due to radiologic under‐estimation of DCIS size which can occur in over 50% of cases . Other studies, similar to the current findings, have shown that the diffuse DCIS growth patterns such as micropapillary and cribriform types, high nuclear grade DCIS with comedo type necrosis and high‐risk VNPI are factors associated with an increased rate of re‐excisions …”
Section: Discussionsupporting
confidence: 84%
“…The consensus panel, having considered data from this meta-analysis and other expert advice concluded that margins of >0mm are sufficient to determine a negative margin when performing BCS for invasive cancer [8]. The disease that is most often closest to the margin in patients undergoing BCS for invasive disease is DCIS [22]. Having different margins for BCS for invasive cancer and for DCIS thus makes little biological sense.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of conventional mammography is limited, missing four in every ten cases of DCIS. Also, when DCIS is detected by conventional mammography and/or ultrasonography, the extent of the lesion is often underestimated . While DCE‐MRI has a good sensitivity of 98% for detecting high‐grade DCIS, its size is frequently overestimated .…”
Section: Future Perspectivesmentioning
confidence: 99%